Three-Dimensional-Bioprinted Embedded-Based Cerebral Organoids: An Alternative Approach for Mini-Brain In Vitro Modeling Beyond Conventional Generation Methods - Rosalba Monica Ferraro; Paola Serena Ginestra; Miriam Seiti; Mattia Bugatti; Gabriele Benini; Luana Ottelli; William Vermi; Pietro Luigi Poliani; Elisabetta Ceretti; Silvia Giliani (Gels)
Cerebral organoids (cORGs) obtained from induced pluripotent stem cells (iPSCs) have become significant instruments for investigating human neurophysiology, with the possibility of simulating diseases and enhancing drug discovery. The current approaches require a strict process of manual inclusion in animal-derived matrix Matrigel® and are challenged by unpredictability, operators’ skill and expertise, elevated costs, and restricted scalability, impeding their extensive applicability and translational potential. In this study, we present a novel method to generate brain organoids that address these limitations. Our approach does not require a manual, operator-dependent embedding. Instead, it employs a chemically defined hydrogel in which the Matrigel® is diluted in a solution enriched with sodium alginate (SA) and sodium carboxymethylcellulose (CMC) and used as a bioink to print neural embryoid bodies (nEBs). Immunohistochemical, immunofluorescence, and gene expression analyses confirmed that SA-CMC-Matrigel® hydrogel can sustain the generation of iPSC-derived cortical cORGs as the conventional Matrigel®-based approach does. By day 40 of differentiation, hydrogel-based 3D-bioprinted cORGs showed heterogeneous and consistent masses, with a cytoarchitecture resembling an early-stage developmental fetal brain composed of neural progenitor cells PAX6+/Ki67+ organized into tubular structures, and densely packed cell somas with extensive neurites SYP+, suggestive of cortical tissue-like neuronal layer formation.